Physiology of elite young female athletes - McManus, A. M.; Armstrong, N. (The Elite young athlete, 2011)
The participation of girls in elite sport has increased exponentially over the past 30 years. Despite these increases a tradition for recruiting boys for exercise studies persistsand our knowledge of the physiologic response to exercise in girls remains limited. Girls` physiology varies with age and maturation and is underpinned by a divergent hormonal milieu which begins early in foetal life. Sexual dimorphism underlies much of the physiologic response to exercise, and becomes most acute during adolescence when boys become taller, heavier, less fat and are more muscular than girls. Young girl athletes are not simply smaller, less muscular boys. The widening sex disparity in responses to exercise during puberty cannot always be accounted for by size. The woeful number of studies on girls and our prior inability to non-invasively study the complexity of the cellular metabolic response to exercise means an integrative understanding of girls` physiological responses to exercise remains elusive. Success in elite sport requires intense training, which for a long time was thought to cause disruption to normal growth and maturation. It would appear that exercise training, without other predisposing factors, is unlikely to cause aberrations to either growth or maturation. Nevertheless, there is clear evidence of a boundary between healthy and unhealthy levels of exertion when coupled with caloric limitation. Sports in which intense training is combined with the need for leanness may predispose girls to increased risk of skeletal and reproductive health problems, and ensuring risk is minimised should be a priority.